The Influence Of The Work Environment, Work Compensation On Turnover Intention Through Job Satisfaction At PT. Albadriyah Wisata - Saputri, Shara Rahayu; Pono, Maat; Mardiana, Ria (Program Pascasarjana STIE Amkop Makassar, 2023)
This research aims to analyze the impact of the work environment, work compensation on turnover intention from job satisfaction at PT Albadriyah Wisata. This research was conducted at PT Albadriyah Wisata involving 50 employees, using a sampling technique purposive sampling, ie selecting a sample according to certain criteria, namely only smartphone use. Data were analyzed in the SEM method on a PLS basis. The research results show that if The work environment has a positive impact on turnover intention. Work compensation has a positive impact on turnover intention. Job happiness is positively influenced by the workplace. Salary and intention to leave the company both have beneficial effects on job satisfaction. Through turnover intention, the workplace has an impact which benefits job satisfaction. Through turnover intention, the workplace has a beneficial impact on job satisfaction. Keywords: work environment, work compensation, turnover intention and job satisfaction